Energy detection based spectrum sensing over enriched multipath fading channels - Bagheri, Alireza; Sofotasios, Paschalis C.; Tsiftsis, Theodoros A.; Ho-Van, Khuong; Loupis, Michael I.; Freear, Steven; Valkama, Mikko (Institute of Electrical and Electronics Engineers Inc., 2016)
Energy detection has been for long constituting the most popular sensing method in RADAR and cognitive radio systems. The present paper investigates the sensing behaviour of an energy detector over Hoyt fading channels, which have been extensively shown to provide rather accurate characterization of enriched multipath fading conditions.
Keywords: Cognitive systems; Diversity reception; Economic and social effects; Energy efficiency; Fading channels